2018
DOI: 10.3389/fphar.2018.01032
|View full text |Cite
|
Sign up to set email alerts
|

Maprotiline Prevents Monocrotaline-Induced Pulmonary Arterial Hypertension in Rats

Abstract: Pulmonary arterial hypertension (PAH) is a progressive disease caused by increased pulmonary artery pressure and pulmonary vascular resistance, eventually leading to right heart failure until death. Soluble guanylate cyclase (sGC) has been regarded as an attractive drug target in treating PAH. In this study, we discovered that maprotiline, a tetracyclic antidepressant, bound to the full-length recombinant sGC with a high affinity (KD = 0.307 μM). Further study demonstrated that maprotiline concentration-depend… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 41 publications
0
5
0
Order By: Relevance
“…21 In this study, MCT was used to establish a rat PAH model, which is widely regarded as classical research method of PAH, especially in the field of drug and pharmacology. 22 The pathological process of this disease model includes induction of chronic inflammation, which leads to the proliferation and migration of PASMCs, and the transformation of endothelial cells, leading to remodeling of the pulmonary artery and an increase in pulmonary artery pressure. 19,23 After baicalin intervention, medium and high doses of baicalin significantly reduced the mPAP and RVSP in rats.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…21 In this study, MCT was used to establish a rat PAH model, which is widely regarded as classical research method of PAH, especially in the field of drug and pharmacology. 22 The pathological process of this disease model includes induction of chronic inflammation, which leads to the proliferation and migration of PASMCs, and the transformation of endothelial cells, leading to remodeling of the pulmonary artery and an increase in pulmonary artery pressure. 19,23 After baicalin intervention, medium and high doses of baicalin significantly reduced the mPAP and RVSP in rats.…”
Section: Discussionmentioning
confidence: 99%
“…PASMC proliferation and pulmonary vascular remodeling are used as a modulator of PAH development and provide the therapeutic target of the disease, and hence novel effective agents and more approaches remain urgently needed for the treatment currently 21 . In this study, MCT was used to establish a rat PAH model, which is widely regarded as classical research method of PAH, especially in the field of drug and pharmacology 22 . The pathological process of this disease model includes induction of chronic inflammation, which leads to the proliferation and migration of PASMCs, and the transformation of endothelial cells, leading to remodeling of the pulmonary artery and an increase in pulmonary artery pressure 19 , 23 .…”
Section: Discussionmentioning
confidence: 99%
“…Maprotiline has been recognized as an antidepressant for a long time, however, several studies have reported its anti-inflammatory function ( Rafiee et al, 2016 ) and ability to relieve pulmonary hypertension ( Tong et al, 2018 ). In this paper, we pointed out that maprotiline has an anticancer effect on HCC.…”
Section: Discussionmentioning
confidence: 99%
“…Due to the low toxicity, good tolerance and adaptability of maprotiline, it is an ideal candidate for functional repurposing. Tong et al (2018) reported that maprotiline may help reduce the progression of pulmonary hypertension in rats, which prompted us to redefine the function of maprotiline.…”
Section: Introductionmentioning
confidence: 99%
“…The rats were sacrificed to perform functional evaluations, and sampling of pulmonary and cardiac tissue was performed for morphometric measurements. Throughout the 21 days of the experimental protocol, no difference in body weight between the groups was recorded, and it was not registered any animal death (Tabata et al, 1997;Tong et al, 2018).…”
Section: Experimental Designmentioning
confidence: 99%